Conservation of Pollinators in Traditional Agricultural Landscapes – New Challenges in Transylvania (Romania) Posed by EU Accession and Recommendations for Future Research - Kovács-Hostyánszki, Anikó (PLoS One, 2016)
Farmland biodiversity is strongly declining in most of Western Europe, but still survives in traditional low intensity agricultural landscapes in Central and Eastern Europe. Accession to the EU however intensifies agriculture, which leads to the vanishing of traditional farming. Our aim was to describe the pollinator assemblages of the last remnants of these landscapes, thus set the baseline of sustainable farming for pollination, and to highlight potential measures of conservation. In these traditional farmlands in the Transylvanian Basin, Romania (EU accession in 2007), we studied the major pollinator groups—wild bees, hoverflies and butterflies. Landscape scale effects of semi-natural habitats, land cover diversity, the effects of heterogeneity and woody vegetation cover and on-site flower resources were tested on pollinator communities in traditionally managed arable fields and grasslands. Our results showed: (i) semi-natural habitats at the landscape scale have a positive effect on most pollinators, especially in the case of low heterogeneity of the direct vicinity of the studied sites; (ii) both arable fields and grasslands hold abundant flower resources, thus both land use types are important in sustaining pollinator communities; (iii) thus, pollinator conservation can rely even on arable fields under traditional management regime. This has an indirect message that the tiny flower margins around large intensive fields in west Europe can be insufficient conservation measures to restore pollinator communities at the landscape scale, as this is still far the baseline of necessary flower resources. This hypothesis needs further study, which includes more traditional landscapes providing baseline, and exploration of other factors behind the lower than baseline level biodiversity values of fields under agri-environmental schemes (AES).